2017
DOI: 10.1016/j.jtho.2016.11.2235
|View full text |Cite
|
Sign up to set email alerts
|

Capture-Based Targeted Ultradeep Sequencing in Paired Tissue and Plasma Samples Demonstrates Differential Subclonal ctDNA-Releasing Capability in Advanced Lung Cancer

Abstract: We have demonstrated that subclones carrying driver mutations are more prone to release DNA. We have also demonstrated the quantitative ability of capture-based sequencing, paving its way for routine utilization in clinical settings.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
119
0
1

Year Published

2017
2017
2021
2021

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 112 publications
(122 citation statements)
references
References 31 publications
2
119
0
1
Order By: Relevance
“…[19] Size, status, and characteristics of cancerous tissues are also highly related. For example, when considering intratumor heterogeneity, subclones carrying driver mutations are more prone to release DNA [20]. However, some researches [21] in non-small cell lung cancer (NSCLC) have indicated that the cfDNA level is correlated with tumor metabolism and reflects tumor biological behaviors rather than tumor burden, potentially because nontumor DNA is also increased during tumor progression due to interactions between tumor cells and adjacent healthy tissue cells [22].…”
Section: Origin Of Ctdnamentioning
confidence: 99%
“…[19] Size, status, and characteristics of cancerous tissues are also highly related. For example, when considering intratumor heterogeneity, subclones carrying driver mutations are more prone to release DNA [20]. However, some researches [21] in non-small cell lung cancer (NSCLC) have indicated that the cfDNA level is correlated with tumor metabolism and reflects tumor biological behaviors rather than tumor burden, potentially because nontumor DNA is also increased during tumor progression due to interactions between tumor cells and adjacent healthy tissue cells [22].…”
Section: Origin Of Ctdnamentioning
confidence: 99%
“…Cell-free DNA was extracted as described. 7 In brief, 10 mL of whole blood was collected and cell-free DNA was extracted from plasma samples by using the QIAamp Circulating Nucleic Acid Kit (Qiagen, Hilden, Germany) according to the manufacturer's instructions.…”
Section: Preparation Of Plasma Cell-free Dnamentioning
confidence: 99%
“…Library preparation was performed as described. 7 Fragments with a size of 200 to 400 base pairs were selected and followed by hybridization with capture probes baits, hybrid selection with magnetic beads, and polymerase chain reaction (PCR) amplification. Indexed samples were sequenced on a Nextseq500 sequencer (Illumina, Inc., San Diego, CA) with paired-end reads.…”
Section: Next-generation Sequencing Library Preparationmentioning
confidence: 99%
“…The NGS library was prepared as described previously (29). Briefly, nucleotide fragments of 200-400 base pairs were selected using Agencourt AMPure beads (Beckman Coulter, Inc.).…”
Section: Next Generation Sequencing (Ngs) Library Preparation and Seqmentioning
confidence: 99%